2016
DOI: 10.1016/j.jphysparis.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Sternopygus macrurus electric organ transcriptome and cell size exhibit insensitivity to short-term electrical inactivity

Abstract: Electrical activity is an important regulator of cellular function and gene expression in electrically excitable cell types. In the weakly electric teleost fish Sternopygus macrurus, electrocytes, i.e., the current-producing cells of the electric organ, derive from a striated muscle lineage. Mature electrocytes are larger than muscle fibers, do not contain sarcomeres, and are driven continuously at frequencies higher than those exerted on muscle cells. Previous work showed that the removal of electrical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Such analyses of adult mEO from several electric fish species have already been reported ( Gallant et al., 2014 ). More recently, Guth et al. (2016) reported transcriptome analysis of regenerating tail showing stage specific gene expression during the developmental process of regenerating mEO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analyses of adult mEO from several electric fish species have already been reported ( Gallant et al., 2014 ). More recently, Guth et al. (2016) reported transcriptome analysis of regenerating tail showing stage specific gene expression during the developmental process of regenerating mEO.…”
Section: Discussionmentioning
confidence: 99%
“…The species has already been extensively used for electrophysiological studies (e.g. Stoddard and Salazar, 2011 ; Matsushita et al., 2013 ) and for transcriptomics ( Gallant et al., 2014 ; Guth et al., 2016 ). Previous studies have shown that the mEO in the B. gauderio develops at the ventral side of the tail myotome in the 6 days post-fertilization (dpf) larvae ( Franchina, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the Teleostei are the largest group of fish on the planet, containing approximately 95% of all living fish species, exhibiting incredible biodiversity and inhabiting waters across the globe (25). The Teleostei are currently being studied for numerous unique attributes including electrical abilities (26)(27)(28), mouthbrooding (29), brackish tolerance (30), cold tolerance (31,32), among others, and now including magnetoreception. The tree was generated using TimeTree (23).…”
Section: Table 1: Evolutionary Changes In the Codon That Encodes Posi...mentioning
confidence: 99%
“…Today, the Teleostei are the largest group of fish on the planet, containing approximately 95% of all living fish species, exhibiting incredible biodiversity and inhabiting waters across the globe [25]. The Teleostei are currently being studied for numerous unique attributes including electrical abilities [26][27][28], mouthbrooding [29], brackish tolerance [30] and cold tolerance [31,32], among others, and now including magnetoreception.…”
Section: Phylogenetic Assessment Of Species With An Epg Homologuementioning
confidence: 99%